The treatment of persistent spinal pain syndrome with epidural pulsed radiofrequency: improvement of the technique - Dario, Alessandro; Capelli, Sergio (Frontiers in Neurology, 2023)
Background In Persistent Spinal Pain Syndrome (PSPS), Pulsed Radiofrequency (PRF) is a used procedure. The results of PRF in PSPS performed with an electrode placed through the sacral hiatus were reported to be successful on pain in only 32% of patients. We have tried to improve the results by applying a new system to PRF. Methods Ten patients were treated with PRF application through a steerable epidural catheter with a reference electrode outside the foramen. This method was named “Optimization Current Flow” (OCF). The duty cycle of PRF was 2 × 10 msec and total exposure time was 150 s. Follow up was planned for 1, 3, and 6 months. The NRS score was considered to be the primary outcome. Results In the first 10 patients treatment was successful (69% of the patients) at 6 months follow-up. Conclusion This new modality of PRF in patients with PSPS seems to be superior to procedures done with a needle. Further prospective double-blind randomized long-term studies with a significant number of patients are required to validate this technique as there is a need to improve PRF results in PSPS.